Straight, bendable and bent organic crystals. Issue 98 (22nd November 2019) - Yadava, Khushboo; Qin, Xian; Liu, Xiaogang; Vittal, Jagadese J.
Abstract : Of the three different types of crystal morphologies of trans -pab, the bent nature is attributed to the small amount of cis -form in the packing of trans -pab, while the elastic bending is due to anisotropic crystal packing. Abstract : trans -4-Phenylazobenzoic acid (pab) crystallized in three different morphologies: long rod-like crystals, bendable long thin crystals, and bent crystals. Of them, the bent crystals were obtained by recrystallizing after subjecting pab to UV-irradiation in solution. A small amount of cis -form in the bent crystals is responsible for the bent nature, while the elastic bending of thin platy crystals can be understood from the crystal packing.